Exceptional architecture, learning processes, and the contradictory performativity of norms and standards. Issue 1 (2nd January 2022) - Grubbauer, Monika; Dimitrova, Venetsiya
ABSTRACT: Large-scale urban projects that make use of exceptional architecture face a number of challenges: namely the scale and complexity of the projects as well as the elevated expectations faced by architectural and engineering firms. Meeting these challenges requires the development and approval of non-standard design and technical solutions. Based on the analysis of four case studies in the German context, we show how the creation of exceptional architecture requires that built environment professionals actively negotiate with established norms and standards in various ways. The learning processes thus enabled are contradictory. On the one hand, knowledge gained in the process of developing innovative solutions remains exclusive and, often, codification and standardization do not occur. On the other hand, in some instances, standards and norms are adapted to inform and guide other projects. In conclusion, this paper argues, norms and standards constitute a contested terrain and are characterized by a contradictory performativity. This paper thus advances wider debates on innovation in the building industry by highlighting the extreme tensions and ambivalent trade-offs that exist between the development of unique and tailor-made solutions for singular buildings and the investment in the standardization of novel products for the built environment.